A Study on the implementation of ISO 9000 quality system and its significance / effect on the product quality of ford vendors / Adenan Che Weel - Che Weel, Adenan (Faculty of Mechanical Engineering, 1999)
Malaysian usually presume that having the ISO 9000 certificate means having a better quality. They also presume that companies practicing ISO 9000 are companies of international standards. This project paper attempts to answer the above by assessing on the impact of ISO 9000 Quality System on the product quality of Ford Vendors. This is accomplished through the analysis of a survey on fifty Ford Vendors who have obtained ISO 9000 certification. The survey is carry out using a mail questionnaires consisting of 21 questions. The analysis focuses on; (ll)The number of reject percentage, (ll)wastage, (lll)production output and (IV)production efficiency. The findings rely entirely on the numbers or the percentage of responses from respondent that being assessed. The finding of the study indicate that the firms which have successfully implemented ISO 9000 Quality System shows an effect on the rejection rate. All of the companies which responded to the questionnaires agreed that ISO 9000 Quality System make their product better, non of them said ISO 9000 Quality System make no different or make their product becomes worse. Many of them agreed that ISO 9000 Quality System has improve total company efficiency by reduce the rejection rate, wastage and increase skill of their workers. Almost all of them said that ISO 9000 Quality System is paying off or rewarding to the company in the long run.